(untitled) (مجلة المنصور, 2022)
Drug taking or trading creates several crimes in addition to being criminal acts in the majority of countries .This has excited in human communities and international organizations increasing interest to find ways that can lessen it if not evading it .This paper which would deal with the subject from various angles : Legislative, social and health-wise, covers the following topics: 1. Legislative Treatment 2. Juridical Treatment 3. Social Treatment 4. Medical Treatment